Satria Honor Payment System at Anteraja of Madegondo Sukoharjo Office: Sistem Pembayaran Honor Satria di Kantor Anteraja Madegondo Sukoharjo - Liberta, Raihan Syach; Naury, Chairullah; Purbiyanto, Eko (Politeknik Harapan Bangsa Surakarta, 2024)
The Satria Honor Payment System at the Anteraja Madegondo Office is an information system that provides data on payment of honorariums for knights or couriers per month in the Madegondo Sukoharjo area. The author in conducting research found a problem, namely that there was no system for paying honorariums for knights at the Anteraja Madegondo office, there was still using a manual system, namely by recording the number of packages sent by knights every day on paper and then these records were collected in a month resulting in less tidy and easy to lose payment data knight's honor at the Anteraja Madegondo office. Therefore the purpose of this research is to solve this problem by creating a system for paying honorariums for warriors, to make it easier for branch heads or leaders to make data recaps for honorary payments so that they are structured and neatly arranged and minimize any payment errors in the form of report data. The author uses the PHP programming language and uses the MySQL database and the method used is the System Development Life Cycle (SDLC) method with the Waterfall model for the process of making this honorary payment system. The system that the author designed will generate payment data in the form of monthly payment of honorarium for knights or couriers.